2008
DOI: 10.1086/591702
|View full text |Cite
|
Sign up to set email alerts
|

Extensively Drug‐ResistantMycobacterium tuberculosisduring a Trend of Decreasing Drug Resistance from 2000 through 2006 at a Medical Center in Taiwan

Abstract: The remaining high prevalence of multidrug-resistant TB and the presence of XDR TB during a trend of decreasing drug resistance are alarming. Continuous surveillance of clinical isolates of M. tuberculosis is needed to identify XDR TB, especially in patients who have a history of TB and have received prior anti-TB treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 23 publications
(29 reference statements)
1
34
3
2
Order By: Relevance
“…M. tuberculosis was identified by a combination of morphology, the growth rate of the colonies, and biochemical tests (10). Drug susceptibility to first-line anti-TB drugs, including isoniazid (0.2 g/ml), rifampin (1.0 g/ml), and ethambutol (5.0 g/ml), and second-line anti-TB drugs, including streptomycin (2.0 g/ ml), kanamycin (6.0 g/ml), and ofloxacin (2.0 g/ml), was tested using modified proportional disk elution methods as described previously (5,11). This study was approved by the Institutional Review Board of Chest Hospital (B-ER-102-164).…”
Section: Selection Of Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…M. tuberculosis was identified by a combination of morphology, the growth rate of the colonies, and biochemical tests (10). Drug susceptibility to first-line anti-TB drugs, including isoniazid (0.2 g/ml), rifampin (1.0 g/ml), and ethambutol (5.0 g/ml), and second-line anti-TB drugs, including streptomycin (2.0 g/ ml), kanamycin (6.0 g/ml), and ofloxacin (2.0 g/ml), was tested using modified proportional disk elution methods as described previously (5,11). This study was approved by the Institutional Review Board of Chest Hospital (B-ER-102-164).…”
Section: Selection Of Isolatesmentioning
confidence: 99%
“…Unfortunately, the widespread use of FQs to treat bacterial infections has led to the emergence of FQ-resistant MDR-TB and extensively drug-resistant TB (XDR-TB; defined as MDR-TB resistant to any FQ and a second-line injectable drug) (4,5), thereby complicating patient care.…”
mentioning
confidence: 99%
“…First-line drugs were reported to be available in all studies, and the vast majority of cohorts had access to all second-line drugs [9][10][11][12][16][17][18][19][20][21][22][23][24]. Linezolid was reported to be available in only three XDR-TB MANAGEMENT G. SOTGIU ET AL. …”
mentioning
confidence: 99%
“…However, the first reports of XDR-TB were in non-HIV-infected individuals from Europe, demonstrating higher risk of death and a longer time required for culture conversion [5,6]. Multiple convenience sample studies from Spain, Iran, Taiwan, and South Korea have been reported, which included treatment outcome data with subnational denominators [7][8][9][10][11][12][13][14]. Population-based MDR-TB and XDR-TB incidence data are now available from the United States [15], as well as from South Korea, Estonia, Peru and Tomsk (Russia), although the proportion of persons with TB infected with HIV in these locations was very low [12][13][14][16][17][18].…”
mentioning
confidence: 99%